Adaptation and validation of the Parents’ Self-stigma Scale into Turkish and its association with parenting stress and parental self-efficacy - Yahya AKTU; Ercan ARAS (BMC Psychology)
Abstract Objectives In the present era, parents frequently stigmatize themselves for their children’s negative behaviors and inadequate social skills. Parents’ self-stigma (PSS) may lead to a decrease in parental self-efficacy and quality of marital and family life. In light of these reasons, the principal objective of this study to assess the validity and reliability of the Turkish version of the PSS Scale (PSSS) as developed by Eaton et al. (2019) and to investigate the indirect effect that parenting stress has on the relationship between PSS and parental self-efficacy. Methods We collected data from a total of 1,118 parents via random sampling, with the first part of the study involving 645 participants (M age = 32.64 ± 7.28) and the second part of the study involving 473 participants (M age = 27.43 ± 9.87). In the first part of the study, we employed structural equation modeling for the confirmatory factor analysis and Pearson’s correlation coefficient for the criterion-related validity, average variance extracted, and composite reliability analyses. Moreover, we calculated Cronbach’s alpha, McDonald’s omega, and Guttman split-half coefficients for the reliability analyses. In the second part of the study, we utilized Hayes’ bootstrapping method to assess the indirect effect of parenting stress on the relationship between PSS and parental self-efficacy. Results The first part of the study confirms the PSSS’s 11-item, 3-factor structure, showing the Turkish form to have acceptable goodness-of-fit indices, and found Cronbach’s alpha for the PSSS to be 0.89. Furthermore, the first part of the study demonstrates a significant negative correlation between marital life satisfaction and PSS. Meanwhile, the second part of the study has determined PSS to be positively related to parenting stress and negatively related to parental self-efficacy. The second part of the study also indicates parenting stress to have an indirect effect on the association between PSS and parental self-efficacy. Conclusions The study indicates the Turkish version of the PSSS to be a valid and reliable instrument in Turkish culture for measuring parents’ PSS levels regarding their children, with higher scores indicating greater PSS. The scale can be effectively used in both research and clinical settings. The study also suggests parental stress to have a possible impact on the association between PSS and parental self-efficacy. Furthermore, addressing the variables of PSS and parenting stress in family-focused interviews and therapeutic interventions may contribute to increasing parental self-efficacy.